Low immunogenicity of malaria pre-erythrocytic stages can be overcome by vaccination - Müller, K; Gibbins, M; Roberts, M; Reyes-Sandoval, A; Hill, AVS; Draper, SJ; Matuschewski, K; Silvie, O; Hafalla, JCR (Wiley, 2021)
Immunogenicity is considered one important criterion for progression of candidate vaccines to further clinical evaluation. We tested this assumption in an infection and vaccination model for malaria pre-erythrocytic stages. We engineered Plasmodium berghei parasites that harbour a well-characterised epitope for stimulation of CD8+ T cells, either as an antigen in the sporozoite surface-expressed circumsporozoite protein or the parasitophorous vacuole membrane associated protein upregulated in sporozoites 4 (UIS4) expressed in exo-erythrocytic forms (EEFs). We show that the antigen origin results in profound differences in immunogenicity with a sporozoite antigen eliciting robust, superior antigen-specific CD8+ T-cell responses, whilst an EEF antigen evokes poor responses. Despite their contrasting immunogenic properties, both sporozoite and EEF antigens gain access to antigen presentation pathways in hepatocytes, as recognition and targeting by vaccine-induced effector CD8+ T cells results in high levels of protection when targeting either antigen. Our study is the first demonstration that poorly immunogenic EEF antigens do not preclude their susceptibility to antigen-specific CD8+ T-cell killing, which has wide-ranging implications on antigen prioritisation for next-generation pre-erythrocytic malaria vaccines.